Mano de obra especializada en los mercados coloniales de Charcas. Bolivia, siglos XVI-XVII - Laura Escobari de Querejazu (Nuevo mundo - Mundos Nuevos, 2011)
The word yanacona had many interpretations in Peruvian and Bolivian historiographies from mid 20th century. This work takes into account the meanings given by Murra and Wachtel, in sense to consider to yanacona like a specialized working craftsman at the pre-Hispanic time, far from the first interpretation that worker considered domestic and, even, slave. It is conceived to yanacona like manpower described at the pre-Hispanic time and the colonial time. Some testimonies induce to think that there were yanaconas miners, urban and rural. The miners gave rise to the working employee, specialized in fusing silver and gold in Potosí. The urban ones caused the appearance of class craftswoman, average loss in the cities of La Paz, Chuquisaca and Potosí, and the rural ones were the Earth workers in the Bolivian plateau. Nevertheless, yanaconas rural in Cochabamba was the beginning of the smallholding, of the mestizo who began like renter of great landowners of this zone.